2022
DOI: 10.3389/fphar.2022.1039553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pheretima aspergillum on reducing fibrosis: A systematic review and meta-analysis

Abstract: Background:Pheretima aspergillum (common name: Earthworm, Chinese name: dilong) has been used in traditional Chinese medicine for thousands of years. Recently, a few scientific studies have investigated the antifibrotic effects of Dilong extract (DE) and produced controversial results. We conducted a meta-analysis to make an informed decision on the antifibrotic effects of Dilong extract.Methods: The studies on antifibrotic effects of Dilong extract published until July 2022 in the scientific databases [PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Rehder and E.H. Wilson ( Zhang et al, 2021 ), displaying significant prevention from tissue injury via antioxidant mechanisms. In addition, two constituents of the ZLHXTY capsule are of animal origin, i.e., H. nipponica Whitman and P. aspergillum (E. Perrier), that have also been shown to act through antioxidant mechanisms ( Li et al, 2021 ; Xu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rehder and E.H. Wilson ( Zhang et al, 2021 ), displaying significant prevention from tissue injury via antioxidant mechanisms. In addition, two constituents of the ZLHXTY capsule are of animal origin, i.e., H. nipponica Whitman and P. aspergillum (E. Perrier), that have also been shown to act through antioxidant mechanisms ( Li et al, 2021 ; Xu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rehder and E.H. Wilson, and Cinnamomum cassia (L.) J. Presl ( Table 1 ). Interestingly, antioxidant activity is common among all of these components ( Yang et al, 2012 ; Rao and Gan, 2014 ; Durazzo et al, 2021 ; Li et al, 2021 ; Samuel et al, 2021 ; Zhang et al, 2021 ; Xu et al, 2022 ). According to TCM theory, the combination of these five drugs work in concert to reduce inflammation, resist oxidation, and fight against aging by enriching Qi, eliminating phlegm and blood stasis, and promoting blood circulation; thereby suitable for the treatment of stroke, atherosclerosis, and other related cardiovascular and cerebrovascular conditions ( Liang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main chemical compositions of Pheretima (Dilong) include protein, amino acid, enzymes, lipids, trace elements and nucleotides. Lumbrukinase is one of the characteristic components of Pheretima, which possess the anticoagulant and thrombolytic effects ( Xu et al, 2022 ). Hirudo (Shuizhi) mainly contains protein polypeptides, pteridines, glycolipids, carboxylic esters and free amino acids.…”
Section: Chemical Profilesmentioning
confidence: 99%
“…Pheretima aspergillum (Megascolecidae) and various derivative products have long been used in traditional oriental medicine to treat high fever, seizures in children, asthma, and high blood pressure. Previous studies have demonstrated that the dried bodies of P. aspergillum (termed Lumbricus) reduce fibrosis, inhibit mitochondrial damage, and relieve asthma [21][22][23]. However, the efficacies of Lumbricus extracts against microgliainduced neuroinflammation and hippocampal cell excitotoxicity have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%